Yeoncheon Palaeolithic Festival: from Hand Axe to Street Dance - Eva IJsveld (EXARC, 2019)
In 1978 a US Army soldier stationed in the North of South Korea discovered several hand axes near Jeongok in the Yeoncheon Province. This was the start of many years of archaeological investigations and eventually the building of the very futuristic Jeongok Prehistory Museum and the organisation of the annual Yeoncheon Paleolithic Festival. This year we were invited, thanks to Wulf Hein and Lee Hanyong, director of the Jeongok Prehistory museum, to join the 27th festival from the 1st – 6th of May 2019. It was a fun and memorable experience.